Curriculum Policy and Practice in Strengthening Islamic Character at Madrasah Tsanawiyah Hubulo Tapa - ahaya, sri meiti anggrainin (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2026)
This study aims to analyze curriculum policies and practices in strengthening Islamic character at Hubulo Tapa Islamic Junior High School (MTs). The focus of the study is directed at how curriculum policies are translated into learning practices, madrasah culture, and co-curricular and extracurricular activities in shaping students' Islamic character. This study uses a qualitative approach with a case study design. Data collection techniques include in-depth interviews with the madrasah principal, teachers, and students, observations of learning activities and madrasah culture, and documentation studies of curriculum documents and madrasah policies. The results show that curriculum policies at MTs Hubulo Tapa are aligned with national education policies and the uniqueness of madrasahs, particularly in the integration of Islamic values. Curriculum practices are realized through values-based learning, teacher role models, religious habits, and character strengthening through Islamic boarding school activities. The implications of this study indicate that consistency between curriculum policies and practices is a key factor in the success of strengthening Islamic character in madrasahs. Keywords: curriculum policy, curriculum practice, Islamic character, Islamic junior high school